Lymph node ratio as best prognostic factor in triple‐negative breast cancer patients with residual disease after neoadjuvant chemotherapy. Issue 9 (25th July 2020) - De la Cruz‐Ku, Gabriel A.; Chambergo‐Michilot, Diego; Valcarcel, Bryan; Rebaza, Pamela; Möller, Mecker; Araujo, Jhajaira M.; Enriquez, Daniel; Morante, Zaida; Razuri, Cesar; Luque, Renato; Saavedra, Antonella; Eyzaguirre, Eduardo; et al.
Abstract: Although lymph node status (ypN) is one of the most important prognostic factors of survival, the lymph node ratio (LNR) has emerged as an equitable factor. We aimed to compare the prognostic value of both ypN and LNR in patients with residual triple‐negative breast cancer (TNBC) after neo‐adjuvant chemotherapy (NAC). This was a retrospective cohort study of patients treated in a tertiary care center during the period 2000‐2014. We stratified the population based on LNR (≤0.20, 0.20‐0.65, and >0.65) and ypN (N1, N2, and N3) status. The overall survival (OS) and progression‐free survival (PFS) were estimated with Kaplan‐Meier curves and the log‐rank + test. We further compared patient mortality and disease recurrence using multivariate Cox regression analysis. We evaluated 169 patients with a median follow‐up of 87 months. At 2 years of follow‐up, patients with low‐risk LNR compared to those with moderate and high risk had a higher PFS (54% vs 31% vs 18%, respectively; P  < .001) and OS (74% vs 64% vs 45%, respectively; P  < .001). Moreover, ypN1 patients compared to ypN2 and ypN3 showed similar results in PFS (53% vs 35% vs 19%, respectively; P  = .001) and OS (73% vs 69% vs 43%, respectively; P  < .001). Compared to the low‐risk population, patients with moderate (hazard ratio [HR]: 3.50; 95% confidence interval [CI]: 1.41‐8.71) and high risk (HR: 6.90; 95% CI: 2.29‐20.77) had a worse PFS. Regarding OS, moderate‐risk (HR: 2.85; 95% CI: 1.10‐7.38) and high‐risk patients (HR: 6.48; 95% CI: 2.13‐19.76) showed considerably worse outcomes. On the other hand, ypN staging was not associated with PFS or OS in the multivariate analysis. The LNR is a better prognostic factor of survival than ypN. The LNR should be considered in the stratification of risk after NAC in patients with TNBC.